Pengaruh Ukuran Perusahaan dan Struktur Modal Terhadap Profitabilitas pada Perusahaan Sektor Finansial yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024 - Nurlaelah Asti; Nurman Nurman; Anwar Anwar; Abdul Rahman; Annisa Paramaswary Aslam (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The financial sector plays a strategic role in supporting national economic stability, making company profitability an important indicator of financial performance sustainability. Differences in business scale and funding decisions among firms are assumed to influence their ability to generate profits. This study aims to analyze the effect of company size and capital structure on profitability in financial sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This research adopts a quantitative approach with an associative research design. Secondary data were obtained from annual financial statements, with a sample of 39 companies selected through purposive sampling based on specific criteria. Panel data regression analysis was employed using EViews 13, preceded by model selection tests. The results indicate that company size, measured by the natural logarithm of total assets, has a positive but insignificant effect on profitability proxied by Return on Assets, suggesting that asset growth has not been accompanied by optimal efficiency improvements. Meanwhile, capital structure measured by the Debt to Equity Ratio shows a negative and significant effect on profitability, indicating that excessive reliance on debt tends to reduce profit levels due to higher financial risk and interest burden. These findings imply that financial sector companies should emphasize efficient asset management and maintain an optimal funding structure to achieve sustainable profitability